Answer:
C
Step-by-step explanation:
We can use the factored form of the quadratic equation, given by:
![y=a(x-p)(x-q)](https://tex.z-dn.net/?f=y%3Da%28x-p%29%28x-q%29)
Where <em>a</em> is the leading coefficient and <em>p</em> and <em>q</em> are the zeros.
We have zeros <em>x</em> = -2 and <em>x</em> = 3. So, let <em>p</em> = -2 and <em>q</em> = 3:
![y=a(x+2)(x-3)](https://tex.z-dn.net/?f=y%3Da%28x%2B2%29%28x-3%29)
Next, we are given that our <em>y-</em>intercept is (0, -30).
In other words, when <em>x</em> = 0, <em>y</em> = -30. So:
![-30=a(0+2)(0-3)](https://tex.z-dn.net/?f=-30%3Da%280%2B2%29%280-3%29)
Solve for <em>a:</em>
<em />
<em />
<em />
Hence, our factored equation is:
![\displaystyle y=5(x+2)(x-3)](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%3D5%28x%2B2%29%28x-3%29)
For the standard form, expand:
![y=5(x^2-3x+2x-6)](https://tex.z-dn.net/?f=y%3D5%28x%5E2-3x%2B2x-6%29)
Simplify:
![y=5(x^2-x-6)](https://tex.z-dn.net/?f=y%3D5%28x%5E2-x-6%29)
Distribute:
![y=5x^2-5x-30](https://tex.z-dn.net/?f=y%3D5x%5E2-5x-30)
Our answer is C.
Answer:
my man dude it is 56
Step-by-step explanation:
Set up the equation
x = the smaller number
x + 15 = the larger number
x + x + 15 =39
solve for x
this will be the smaller number
add 15 to get the larger number
3 years ago, the cost was $600.
So 5 years from now, the cost will be $600 + 8 * $150 = $1800.
Answer:
It will give you the opposite sign.
Step-by-step explanation:
If you multiply two negatives you will end up with a positive and vice versa with positives. The same thing applies to dividing.